Pontic design and its effects on the health of the gingiva - Bukhari, Meisan Ali; Aldossari, Ali Mohammed; Alyami, Ibrahim Mohammed; Al Shari, Abdullah Hassan; Al Huwaidi, Abdulmunem Abdulaziz; Alzaid, Salman Youssef; Alqahtani, Ali Mohammad; Musayri, Mohammed Ibrahim; AlShahrani, Yahya Mohammed (International Journal Of Community Medicine And Public Health, 2022)
A pontic is an artificial tooth that substitutes a lost natural tooth, preserves its function, and typically fills the space left by the actual crown. Sanitary/hygienic and modified sanitary/hygienic designs do not contact the alveolar mucosa. On the other hand, ridge lap, modified ridge lap, ovate, modified ovate, and conical are designs that maintain contact with the mucosa. The ideal biological properties to be taken into consideration while designing pontics are periodontal health, access for oral hygiene, no food trapping and occlusal harmony. Accumulation of dental plaque has been implicated in the onset of gingival and periodontal disease as well as caries in the vicinity of the fixed restoration. The connection of the pontic to the supporting crowns must be constructed in such a way as to make a flushable area in the direction of the gingiva, in order to ensure that this area can be cleaned by toothbrushing and flossing but not the large triangular spaces that make it easy for food particles to cling. Modified ridge lap and ovate types, out of all the pontic shapes described below, exhibit convex cleansable faces. Ovate pontics are most effective for use in anterior regions, while the modified ridge lap design can be utilized predominantly in fixed partial denture designs posteriorly. The important etiological factor for gingivitis, periodontitis and peri-implantitis is bacterial colonization which is impacted by the individual's immunologic response and genetic predisposition in addition to dental care practices and pontic design. It is believed that no matter what the material of the pontic is, it must provide a highly polished intaglio surface to help floss slide through and make contact with the full base of the pontic in order to minimize plaque accumulation.